Analysis and future outlook of intra-Asia shipping - Chow, Chun Ho (2014)
Asia, being the largest and most populous continent, is able to create a huge demand for the international market. And with the world’s attention shifted towards Asia in recent years, the shipping industry began to venture into the viability of having Asia as a market itself. Intra-Asia dry bulk trade looks promising ahead as demand for bulk commodities, fuelled by emerging economies, within the region remains high. Politics and government policies that affect dry bulk trade have aplenty uncertainties which can have adverse impact on trade. The recent raw minerals export ban by Indonesia, adds to the worrying vessel oversupply issue. However, it also creates opportunities for others.